Detachment and transport of composition B detonation particles in rills - Cubello, Favianna; Karls, Benjamin; Kadoya, Warren; Beal, Samuel; Polyakov, Viktor; Dontsova, Katerina (Frontiers in Environmental Science, 2024)
The partial detonation of munitions used in military exercises leaves behind energetic particles on the surface of soil. Energetic particles deposited by incomplete detonations can then dissolve and be transported by overland flow and potentially contaminate ground and surface waters. The objective of this study was to evaluate the mechanisms of transport of Composition B, a formulation that includes TNT (2,4,6-trinitrotoluene) andRDX (hexahydro-1,3,5-trinitro-1,3,5-triazine) during overland flow. The transport of Composition B was examined using a rill flume with three flow rates (165-, 265-, and 300-mL min -1 ) and four energetic particle sizes (4.75-9.51 mm, 2.83-4.75 mm, 2-2.83 mm, and <2 mm). After each erosion simulation, energetic particles remaining on the soil surface were measured along with energetics dissolved in runoff, in suspended sediment, and in infiltration. Smaller particle sizes led to greater transport in both solution and sediment. The properties of the energetic compounds also influenced transport. More TNT was transported in runoff than RDX, likely due to TNT's higher solubility and dissolution rates, however, overall, dissolved energetics in runoff and infiltration accounted for very little of the transported energeticstotal transport. Most transport of Composition B was the result of the physical movement of energetic particles and flakes by erosion forces. This study's results allow for improved prediction of Composition B transport during overland flow.